Health Information-Seeking Behavior and Sexual Literacy: Insights from Iranian Medical College Students - Bagheri, Mohaddeseh; Bagherzadeh, Razieh; Mokhtari, Heidar; Khosravi*, Abdolrasool (Journal of Medical Library and Information Science, 2024)
Introduction: To enhance the sexual health literacy of young people, particularly students, it is essential to focus on how they seek health information online. This study aimed to investigate the relationship between sexual health literacy level and web-based health information-seeking behavior of Iranian medical students. Methods: This cross-sectional research employed stratified random sampling method for the distribution of questionnaires to Bushehr University of Medical Sciences students in Bushehr, Iran. A total of 422 questionnaires were distributed, and 387 were completed, representing a response rate of 91.7%. Data were collected using the normalized questionnaires of web-based health information-seeking behavior and sexual health literacy of Iranian adults and analyzed using Pearson’s correlational test and linear regression analysis in SPSS 22 software. Results: The research showed that students have relatively higher rates of sexual health literacy and web-based health information-seeking behavior. Despite the desirability of sexual health literacy and web-based health information-seeking behavior, as a whole, the analysis and evaluation component of sexual health literacy and the sharing and application components of web-based health information-seeking behavior of students were at an average level. In addition, there was a direct and meaningful relationship between web-based health information-seeking behavior and sexual health literacy (P<0.001). All web-based health information-seeking behavior components, but familiarity with the Internet, predicted sexual health literacy (P<0.001). Conclusion: Health officials and policymakers in the country must develop appropriate and written educational programs to improve the level of health information-seeking behavior, specifically in sharing and appliying sexual information, as well as sexual health literacy, particularly in the analysis and evaluation aspects among the visited groups.